The Role of Culture Awareness in Teaching English as a Foreign Language - Tarigan, Fatin Nadifa; Nadhira, Ahmad (Lembaga Komunikasi dan Informasi Dosen, 2023)
Many modern researchers have explained the need and rationale for a wide range of cultural studies in combination with foreign language teaching. However, questions remain as to the content selection, forms of work and technologies that provide students with active interactions, and complete immersion. The paper focuses on the research questions: How can cultural knowledge and understanding be incorporated into the context of English language teaching? Findings indicates that including a culturally appropriate approach to foreign language instruction into professional training improves the art and cultural awareness of aspiring English teachers by allowing them to apply their acquired cultural knowledge in cross-cultural communication scenarios. It helps people become more focused on their jobs. Their motivation is increased, and an environment of openness and inquiry is fostered via cultural studies. The questionnaire was completed by 24 respondents.Keywords : pedagogic competence, teachers, cooperative learning